2013
DOI: 10.3109/0886022x.2012.761038
|View full text |Cite
|
Sign up to set email alerts
|

HLA DRB1 Alleles and Hepatitis C Virus Infection in Chronic Kidney Disease Patients

Abstract: T cell responses against HCV are regulated by the host's human leukocyte antigen (HLA) alleles, which thus are ideal candidate genes to investigate for associations with HCV susceptibility. We aimed to identify associations of HLA DRB1 Ã alleles with HCV infection in a high risk of exposure population, chronic kidney disease (CKD) patients on dialysis, and to study any possible relationships with allele zygosity. The study population comprised 110 HCV infected and 143 HCV uninfected CKD patients undergoing reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Previous studies have demonstrated a heterozygote advantage for classical HLA class II genes in the context of human HBV infection ( 43 ), HBV-associated hepatocellular carcinoma ( 45 ), and in patients with ulcerative colitis ( 44 ). Moreover, a heterozygote advantage has also been reported by Hraber et al ( 46 ) in the context of HCV infection but this could not be confirmed in an independent study by Shaheen et al ( 47 ). A heterozygote advantage in classical HLA class I loci has been documented in the context of HIV infection, as this virus produces escape variants during chronic infection at a considerable frequency ( 1 ).…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies have demonstrated a heterozygote advantage for classical HLA class II genes in the context of human HBV infection ( 43 ), HBV-associated hepatocellular carcinoma ( 45 ), and in patients with ulcerative colitis ( 44 ). Moreover, a heterozygote advantage has also been reported by Hraber et al ( 46 ) in the context of HCV infection but this could not be confirmed in an independent study by Shaheen et al ( 47 ). A heterozygote advantage in classical HLA class I loci has been documented in the context of HIV infection, as this virus produces escape variants during chronic infection at a considerable frequency ( 1 ).…”
Section: Discussionmentioning
confidence: 81%
“…For the meta-analysis aimed to determine the association of HLA DRB*12 with ESRD, eighteen studies were selected ( Ademović-Sazdanić & Vojvodić, 2019 ; Almogren, Shakoor & Hamam, 2012 ; Bhallil et al, 2017 ; Chowdhry, Makroo & Kumar, 2016 ; Dai et al, 2015a ; Hamdi, Al-Hababi & Eid, 2014 ; Hieu, Ha & Nghi, 2019 ; Karahan et al, 2009 ; Kodaz, Akdeniz & Cengiz, 2017 ; Mosaad et al, 2014 ; Nassar et al, 2017 ; Nassar, Al-Shamahy & Masood, 2015 ; Pan et al, 2019 ; Patel et al, 2013 ; Pérez-Luque et al, 2000 ; Shaheen et al, 2013 ; Shang et al, 2016 ). These analyses showed a cumulative OR of 1.05, 95% CI [0.94, 1.18] in a random effect model for ESRD patients compared with healthy individuals ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Significant heterogeneity was found among the studies (Chi 2 = 28.01, P = 0.04, I 2 = 39%). Seven studies showed a positive association between HLA DRB*13 and ESRD ( Chowdhry, Makroo & Kumar, 2016 ; Hamdi, Al-Hababi & Eid, 2014 ; Mosaad et al, 2014 ; Nassar et al, 2017 ; Nassar, Al-Shamahy & Masood, 2015 ; Pérez-Luque et al, 2000 ; Shaheen et al, 2013 ). However, there was no statistically significant negative association between ESRD and DRB*13 (OR = 0.90, CI [0.81, 1.01]) ( P = 0.07) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, HLA-associated alleles in Egyptian patients with hepatitis C have been studied using current methods include Sequence-Specific Oligonucleotide Probe Hybridization (SSOPH), Sequence-Specific Primers (SSP) and PCR-SSO luminex technology which are costly and require multiple steps (Shaker et al, 2013;Shaheen et al, 2013;Yosry et al, 2011).…”
Section: Introductionmentioning
confidence: 99%